What female pop-folk celebrity in south-east Europe tells postsocialist feminist media studies about global formations of race. Issue 3 (2nd April 2020) - Baker, Catherine
ABSTRACT: Feminist media studies of postsocialism are well practised at explaining how ideologies of gender and nation reinforce each other amid neoliberal capitalism on Europe's semi-periphery. They extend this, by critiquing media marginalization of Roma, into addressing regional formations of race. Yet they rarely go on to contextualize the region's place within "race" as a global structure of feeling, or how transnational processes of "race in translation" operate in postsocialism—as necessary as this would be to fulfil ever-more-frequent calls to combine postsocialist and post-colonial analytical lenses. Vestiges of racial exceptionalism thus still often characterize postsocialist studies despite Anikó Imre's intervention against them more than a decade ago. This paper traces how south-east European pop-folk music's politics of representation, "modernity" and "Balkanness" interact with aesthetics of ethnic/racial ambiguity in Western female celebrity to translate globalized, racialized tropes of exoticism into postsocialist national media cultures. By explaining how pop-folk female celebrity translates the transnational racialized aesthetics of so-called "ethnic simultaneity" into postsocialist glamour, the paper puts Imre's intervention against racial exceptionalism into practice, expanding postsocialist feminist media studies' conceptual tools for understanding the regional politics of ethnicity into engagement with the global politics of race.